Base cloth for air bag
By coating the aqueous polyurethane resin composition of branched polycarbonate alcohol and cationic hydrophilic groups on the air bag base cloth, the contradiction between lightweight and high air tightness is solved, and an air bag base cloth with high air tightness and good storage performance is achieved.
Patent Information
- Application Number
- JP2023117617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
The prior art is difficult to achieve high airtightness and heat resistance of the airbag base cloth without increasing the thickness and weight of the base cloth, while meeting lightweight and good storage performance.
An air-bag base cloth containing a hardened aqueous polyurethane resin composition is used to form a polyurethane resin coating with a branched chain structure by coating an aqueous polyurethane resin containing polyisocyanate, branched chain polycarbonate alcohol, cationic hydrophilic groups and at least two active hydrogen compounds on one side of the base cloth to form a polyurethane resin coating with a branched chain structure to improve air tightness and storage performance.
High airtightness and good storage performance of the airbag base cloth with a small coating volume are achieved while maintaining lightweight properties.
Smart Images

Figure 2025014788000004 
Figure 2025014788000001 
Figure 2025014788000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a base fabric for an airbag. More specifically, the present invention relates to a base fabric for an airbag in which airtightness and storage property are improved even with a small amount of coating by using a urethane resin having excellent adhesion as a coating material. [Background technology]
[0002] Airbags are used to reduce the impact of collisions during accidents and the contact between in-vehicle equipment and the human body. To achieve this, airbags are required to be airtight. In addition, explosive inflators are often used to deploy airbags, and the base fabric used in airbags is required to have high heat resistance to withstand the high-temperature gas and residues that are generated. To solve these problems, a method of applying a coating material to the surface of the base fabric used in airbags is widely used to improve the airtightness and heat resistance.
[0003] A recent trend is that, due to the rise in global safety standards, the number of locations where airbags are installed is increasing, and the size of the airbags themselves is increasing to expand the range of protection. On the other hand, the space available for airbags is limited due to the expansion of vehicle interior space, and there is a strong demand for lighter components used in vehicles to contribute to improved fuel efficiency. To meet these demands, high packability and light weight are considered important items, and there is a demand for a base fabric that is lightweight and has good packability even when coated.
[0004] Patent Document 1 below discloses an airbag fabric that reduces the bag weight by using a urethane resin instead of the silicone resin that is widely used as a coating material for airbags.
[0005] The following Patent Document 2 discloses an airbag fabric that has high slippage resistance and a small folded thickness by using a urethane resin as a coating material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-168131 A [Patent Document 2] JP 2009-62643 A Summary of the Invention [Problem to be solved by the invention]
[0007] The coating material applied to the base fabric of an airbag plays a role in improving airtightness and heat resistance. Generally, the amount of coating is proportional to the performance, and in order to meet the airtightness and heat resistance required for the base fabric for an airbag, a certain amount of coating material must be applied. On the other hand, the coating material thickens the base fabric, and the rigidity of the coating material is added to the base fabric, making the base fabric harder and worsening the storability. In addition, the weight of the coating material increases the weight of the base fabric, and the lightness is deteriorated. There is a problem that the development of a base fabric that can improve the storability and lightness while meeting the required standards for the base fabric is desired. Patent Document 1 discloses a method for satisfying the airtightness of a base fabric even with a small amount of coating by using a coating material with excellent adhesion to the base fabric, but only evaluates the air permeability at a low pressure of 125 Pa, and does not disclose anything about the air permeability at high pressures of 50 kPa or more required for airbag base fabrics. 2 Only the results of 20g / m 2 There is no disclosure as to whether high airtightness can be achieved with a coating weight of less than this, and there remains room for improvement in terms of maintaining airtightness at low coating weights and under high pressure. The following Patent Document 2 discloses a method for providing a lightweight and flexible base fabric by using a coating material with high slippage resistance, but only evaluates the breathability at a low pressure of 125 Pa, and does not disclose anything about the breathability at a high pressure of 50 kPa or more, which is required for airbag base fabrics. There is also room for improvement in terms of slippage resistance.
[0008] In view of the level of the prior art, the problem to be solved by the present invention is an airbag base fabric having a coating material, which can achieve high airtightness and storage ability even with a small amount of coating. Is to provide a base fabric for an airbag. [Means for solving the problem]
[0009] As a result of intensive research to solve the above problems, the present inventor unexpectedly discovered that the airtightness and storage property of the airbag base fabric can be improved even with a small amount of coating by using a urethane resin with excellent adhesion as a coating material, and has made the present invention.
[0010] That is, the present invention is as follows. [1] An airbag fabric comprising a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, the aqueous urethane resin composition having the following properties: (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogens; The isocyanate-terminated prepolymer obtained by reacting the above as an essential component with the following: (d) a polyamine having two or more amino groups and / or imino groups; and the cured product of the aqueous urethane resin composition has a viscosity of 5 g / m 2 ~15g / m 2 An airbag base fabric, characterized in that it is coated. [2] The airbag fabric according to [1] above, wherein the (b) polycarbonate diol having a branched structure has a structural unit derived from a diol having a branched structure and 3 to 10 carbon atoms. [3] The airbag fabric according to [1] or [2], wherein the (b) polycarbonate diol having a branched structure has a structural unit derived from a diol having 3 to 10 carbon atoms and a structural unit derived from a diol having a linear structure and 3 to 10 carbon atoms. [4] The aqueous urethane resin composition further comprises, in addition to the (a), (b), and (c), the following: (e) trihydric or higher alcohols; The airbag fabric according to any one of the above [1] to [3], which contains a urethane resin obtained by reacting the above (d) with an isocyanate-terminated prepolymer obtained by reacting the above (a) with the above (b). [5] The airbag fabric according to any one of [1] to [4], wherein the airbag fabric has a slip resistance of 1000N to 2500N. [6] The air permeability of the airbag fabric under a differential pressure of 100 kPa is 0.01 l / cm 2 The airbag fabric according to any one of [1] to [5] above, wherein the viscosity is 0.1 to 1.0 MPa. [7] The airbag fabric according to any one of [1] to [6], wherein the airbag fabric is made of yarn having a fineness of 200 dtex to 800 dtex. [8] The airbag fabric according to any one of [1] to [7], wherein the fibers constituting the fabric are polyethylene terephthalate fibers or polyhexamethylene adipamide fibers. [9] The airbag fabric according to any one of [1] to [8], wherein the tensile strength of the fibers constituting the fabric is 7.5 cN / dtex to 11.5 cN / dtex.
[10] The weight of the remainder excluding the cured product of the aqueous urethane resin composition is 150 g / m 2 ~300g / m 2 The airbag fabric according to any one of the above [1] to [9], Effect of the Invention
[0011] The airbag fabric according to the present invention has excellent airtightness and storage capacity even when the coating material is applied in a small amount. [Brief description of the drawings]
[0012] [Figure 1] 1 shows a method of folding a base fabric in a storage ease evaluation according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described in detail. One embodiment of the present invention provides an airbag fabric comprising a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, the aqueous urethane resin composition having the following properties: (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogens; The isocyanate-terminated prepolymer obtained by reacting the above as an essential component with the following: (d) a polyamine having two or more amino groups and / or imino groups; and the cured product of the aqueous urethane resin composition has a viscosity of 5 g / m 2 ~15g / m 2 The airbag fabric is characterized in that it is coated.
[0014] The term "aqueous" in the aqueous urethane resin composition applied to the airbag fabric of this embodiment means that after the urethane resin is emulsified and dispersed in water to prepare an emulsion dispersion with a resin concentration in water of 40 mass%, this emulsion dispersion can be left to stand for 12 hours at 20° C. without separation or sedimentation being observed. In this embodiment, the aqueous urethane resin composition is applied to the fabric and cured to form a coating material.
[0015] The polyisocyanate component (a) used in the urethane resin applied to the airbag fabric of this embodiment is not particularly limited, and aromatic, aliphatic and alicyclic polyisocyanates that have been generally used in the past can be used. Specifically, examples of aromatic polyisocyanates that can be used include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dichloro-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, tetramethylene xylylene diisocyanate, xylylene diisocyanate, etc., and examples of aliphatic polyisocyanates that can be used include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, tetramethylene xylylene diisocyanate, xylylene diisocyanate, etc. Examples of the reisocyanate that can be used include tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of the alicyclic polyisocyanate that can be used include isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate, norbornane diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane. These polyisocyanates may be used alone or in combination of two or more. From the viewpoint that the resulting urethane resin is non-yellowing, aliphatic polyisocyanates and alicyclic polyisocyanates are preferred.
[0016] The polycarbonate diol component having a branched structure (b) used in the urethane resin applied to the airbag fabric of this embodiment is generally a compound obtained by 1) a reaction between a diol component and a chlorocarboxylic acid, 2) a reaction between a diol component and a phosgene, 3) a reaction between a diol component and a cyclic carbonate, 4) a condensation reaction of a dicarbonate compound, etc., and has a structural unit derived from a diol having a branched structure. The polycarbonate diol component having a branched structure (b) used in the urethane resin applied to the airbag fabric of this embodiment may be only a structural unit derived from a diol having a branched structure, or may also contain a structural unit derived from a diol having a linear structure, and more preferably has a structural unit derived from a diol having a branched structure and a carbon number of 3 to 10, and most preferably has a structural unit derived from a diol having a branched structure and a carbon number of 3 to 10 and a linear structure. Examples of structural units derived from diols having 3 to 10 carbon atoms and having a branched structure include 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl-1,8-octanediol, neopentyl glycol, etc. Examples of structural units derived from diols having 3 to 10 carbon atoms and having a linear structure include 1,10-decanediol, 1,9-nonanediol, 1,8-octanediol, 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, 1,3-propanediol, etc. The number average molecular weight of the branched polycarbonate diol component (b) used in the urethane resin applied to the airbag fabric of this embodiment is preferably 500 to 6000, more preferably 800 to 4000. When the number average molecular weight is equal to or higher than the lower limit, the airbag fabric has excellent slip resistance and storability, while when the number average molecular weight is equal to or lower than the upper limit, the airbag fabric has excellent breathability. The ratio of (b) to the total mass of the compound having a hydroxyl group capable of reacting with an isocyanate group in the urethane resin is preferably 10 to 99.7% by mass, more preferably 30 to 99.6% by mass, from the viewpoint of slippage resistance and storability of the airbag fabric. When the ratio of (b) is equal to or more than the lower limit, the airbag fabric has excellent slippage resistance and storability. The compound having a hydroxy group capable of reacting with an isocyanate group is (b), diols other than (b) described below, (c) and (e). The branched diol-derived structural unit in the diol-derived structural unit (b) is preferably 10 to 100 mol %, more preferably 30 to 100 mol %, from the viewpoints of slippage resistance, breathability, and packability of the airbag fabric. When the proportion of (b) is less than 99.7% by mass, diols other than (b) that can be used include polyether-based diols, polyester-based diols, polycarbonate-based diols other than (b), and diols having a number average molecular weight of 200 or less.
[0017] As the polyether diol, a polymer of an alkylene oxide such as ethylene oxide, propylene oxide, or butylene oxide is used. Such a polymer may be a homopolymer of one type of alkylene oxide, or a copolymer of two or more types of alkylene oxide. In the case of a copolymer, it may be a random polymer or a block polymer. The number average molecular weight of such a polyether diol is preferably 400 to 5000. In addition, as the polyether diol, a compound in which one or more alkylene oxides are added to a dihydric alcohol having a number average molecular weight of 200 or less can also be used. As the dihydric alcohol having a number average molecular weight of 200 or less, ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, nonanediol, neopentyl glycol, etc. are used.
[0018] Examples of polyester diols include diol components such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycols having a number average molecular weight of 300 to 1,000, dipropylene glycol, tripropylene glycol, bishydroxyethoxybenzene, 1,4-cyclohexanedimethanol, bisphenol A, bisphenol S, hydrogenated bisphenol A, hydroquinone, or alkylene oxide adducts thereof, and dimers. Examples of the polyester diols that can be used include polyester diols obtained by dehydration condensation reaction with dicarboxylic acid components such as cyclic ester compounds such as cyclic ester compounds, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, maleic anhydride, fumaric acid, 1,3-cyclopentanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bisphenoxyethane-p,p'-dicarboxylic acid, dicarboxylic acid anhydrides or ester-forming derivatives, polyester diols obtained by ring-opening polymerization reaction of cyclic ester compounds such as ε-caprolactone, and polyester diols copolymerized with these. Examples of polycarbonate-based diols other than (b) include polycarbonate-based diols obtained by the reaction of one or more diols selected from glycols such as 1,10-decanediol, 1,9-nonanediol, 1,8-octanediol, 1,6-hexanediol, 1,5-pentanediol, 1,4-butanediol, 1,3-propanediol, and diethylene glycol with chlorocarboxylic acid, phosgene, cyclic carbonate, etc., or by the condensation reaction of a dicarbonate compound. Examples of the diol having a number average molecular weight of 200 or less include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, nonanediol, and neopentyl glycol. These diols other than (b) may be used alone or in combination of two or more.
[0019] (b) Examples of polycarbonate diols having a branched structure include the following. Polycarbonate diols derived from 3-methyl-1,5-pentanediol / 1,6-hexanediol (Kuraray Polyol C-1090 (number average molecular weight: 1000), Kuraray Polyol C-2090 (number average molecular weight: 2000), Kuraray Polyol C-3090 (number average molecular weight: 3000), Kuraray Polyol C-5090 (number average molecular weight: 5000) manufactured by Kuraray Co., Ltd.). Polycarbonate diol derived from 2-methyl-1,3-propanediol (ETERNACOLL UP-100 (number average molecular weight: 1000), ETERNACOLL UP-200 (number average molecular weight: 2000) manufactured by UBE Corporation). Polycarbonate diol derived from 2-methyl-1,8-octanediol / 1,9-nonanediol (Kuraray Polyol C-1015N (number average molecular weight: 1000), Kuraray Polyol C-2015N (number average molecular weight: 2000), Kuraray Polyol C-1065N (number average molecular weight: 1000), Kuraray Polyol C-2065N (number average molecular weight: 2000) manufactured by Kuraray Co., Ltd.). Polycarbonate diol derived from 2,2-dimethyl-1,3-propanediol (BENEBiOL NL1005B (number average molecular weight: 1000), BENEBiOL NL2005B (number average molecular weight: 2000), BENEBiOL NL1030B (number average molecular weight: 1000), BENEBiOL NL2030B (number average molecular weight: 2000) manufactured by Mitsubishi Chemical Corporation)
[0020] The (c) compound having an anionic hydrophilic group and at least two active hydrogens used in the urethane resin applied to the airbag fabric of this embodiment is a compound having an anionic hydrophilic group such as a carboxy group, a carboxylate group, a sulfo group, a sulfonate group, etc., and two or more active hydrogen-containing groups such as a hydroxy group. Specifically, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, 2,2-dimethylolvaleric acid, dihydroxymaleic acid, 2,6-dihydroxybenzoic acid, etc. are used. By copolymerizing this (c) compound having an anionic hydrophilic group and at least two active hydrogens, a self-emulsifying urethane resin is obtained. The content of anionic hydrophilic groups in the urethane resin is preferably 0.3 to 3 mass%, more preferably 0.5 to 2.5 mass%, from the viewpoint of emulsion stability and storage stability. When the content of anionic hydrophilic groups is equal to or more than the lower limit, the emulsion stability and storage stability of the urethane resin tend to be excellent, and the urethane resin can be used stably. On the other hand, when the content is equal to or less than the upper limit, the urethane resin has excellent flexibility, and the slip resistance and storage property of the airbag base fabric are improved.
[0021] Examples of the polyamine having two or more amino groups and / or imino groups (d) used in the urethane resin applied to the airbag fabric of this embodiment include diamines such as ethylenediamine, propylenediamine, tetramethylenediamine, hexamethylenediamine, diaminocyclohexylmethane, hydrazine, 2-methylpiperazine, isophoronediamine, norborane di((amine, diaminodiphenylmethane, tolylenediamine, and xylylenediamine; polyamines such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, and iminobispropylamine; diprimary Amidoamines derived from amines and monocarboxylic acids; water-soluble amine derivatives such as monoketimines of diprimary amines; hydrazine derivatives such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, itaconic acid dihydrazide, 1,1'-ethylene hydrazine, 1,1'-trimethylene hydrazine, and 1,1'-(1,4-butylene)dihydrazine, etc. may be used. These polyamines may be used alone or in combination of two or more. The amount of (d) used is preferably an amount that contains 0.6 to 1.2 equivalents of amino groups and the like relative to the free isocyanate groups of the isocyanate-terminated prepolymer described below.
[0022] The urethane resin applied to the airbag fabric of this embodiment is obtained by reacting the isocyanate-terminated prepolymer obtained by reacting the above-mentioned (a), (b), and (c) as essential components with the above-mentioned (d). It is usually obtained as a water dispersion.
[0023] (Isocyanate-terminated prepolymer) In the production of the isocyanate-terminated prepolymer, a diol other than (b) may be used in combination, and further, (e) a trihydric or higher alcohol component may be used in combination. (e) Trihydric or higher alcohols include trimethylolpropane, pentaerythritol, and sorbitol. Polyalkylene polyamines or compounds having a number average molecular weight of 500 or less obtained by adding one or more alkylene oxides to the above-mentioned trihydric or higher alcohols can also be used as (e). Examples of polyalkylene polyamines include ethylene diamine, diethylene triamine, and triethylene tetramine. Examples of the alkylene oxides include alkylene oxides having 1 to 4 carbon atoms (specifically, ethylene oxide, propylene oxide, butylene oxide, etc.). Among the trihydric or higher alcohols, trihydric to tetrahydric alcohols are preferred, and trihydric alcohols are more preferred, from the viewpoint of the folding performance of the airbag fabric. The proportion of the mass of (e) relative to the total mass of (b), the diol other than (b), (c) and (e), which are compounds having a hydroxy group capable of reacting with an isocyanate group, is preferably 0.1 to 5 mass %, and more preferably 0.3 to 3 mass %, from the viewpoints of the slippage resistance, breathability and storability of the airbag. When the proportion of (e) is equal to or greater than the lower limit, the air permeability of the airbag fabric is excellent, whereas when the proportion is equal to or less than the upper limit, the airbag fabric is excellent in slip resistance and storability.
[0024] The method for producing the isocyanate-terminated prepolymer is not particularly limited, and a conventionally known one-stage so-called one-shot method, a multi-stage isocyanate polyaddition reaction method, or the like can be used. The reaction temperature is preferably 40 to 150° C. In this case, if necessary, a reaction catalyst such as dibutyltin dilaurate, stannous octoate, dibutyltin di-2-ethylhexoate, triethylamine, triethylenediamine, N-methylmorpholine, bismuth tris(2-ethylhexanoate), or diazabicycloundecene, or a reaction inhibitor such as phosphoric acid, sodium hydrogen phosphate, paratoluenesulfonic acid, adipic acid, or benzoyl chloride may be added. During or after the reaction, an organic solvent that does not react with isocyanate groups may be added. Examples of such organic solvents include acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, dimethylformamide, dimethyl sulfoxide, toluene, xylene, ethyl acetate, butyl acetate, and methylene chloride. Among these organic solvents, methyl ethyl ketone, toluene, and ethyl acetate are particularly preferred. In addition, these organic solvents can be removed by heating and reducing pressure after the prepolymer is emulsified and dispersed and chain-extended. In producing an isocyanate-terminated prepolymer, the molar ratio (NCO / OH) of the raw material isocyanate groups to hydroxy groups in the nonvolatile content of the prepolymer is preferably 1.1 to 2, and more preferably 1.25 to 1.7. By adjusting the molar ratio of the raw material isocyanate groups to hydroxy groups within the above range, an isocyanate-terminated prepolymer having a desired free isocyanate group content can be obtained.
[0025] The free isocyanate group content in the isocyanate group-terminated prepolymer is preferably 0.2 to 5% by mass, more preferably 1 to 4% by mass. When the free isocyanate group content is equal to or higher than the lower limit, the isocyanate group-terminated prepolymer has an appropriate viscosity during production, so that the amount of organic solvent used can be reduced and sufficient emulsion dispersion can be achieved. On the other hand, when the free isocyanate group content is equal to or lower than the upper limit, there is little change in the balance of water solubility after emulsion dispersion and after chain extension by (d) polyamine, and the urethane resin has excellent storage stability over time or processing stability. (a) Polyisocyanate, (b) Polycarbonate diol having a branched structure, (c) Compound having an anionic hydrophilic group and at least two active hydrogens, and (e) Trivalent or higher alcohol all have multiple reaction sites. The isocyanate-terminated prepolymer obtained by reacting these has a complex structure and cannot be directly represented by a general formula (structural formula).
[0026] (Neutralized product of isocyanate-terminated prepolymer) The neutralized product of the isocyanate-terminated prepolymer is a product in which the anionic hydrophilic groups in the isocyanate-terminated prepolymer are neutralized. The neutralized product of the isocyanate-terminated prepolymer may be produced by (i) neutralizing the anionic hydrophilic group in the isocyanate-terminated prepolymer by a known method, or by (ii) mixing (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least two active hydrogens, and (d) a tri- or higher hydric alcohol, neutralizing the anionic hydrophilic group of (c) the compound having an anionic hydrophilic group and at least two active hydrogens by a known method, and then reacting the neutralized (c) compound having an anionic hydrophilic group and at least two active hydrogens, (a) the polyisocyanate, (b) the polycarbonate diol having a branched structure, and the tri- or higher hydric alcohol (e). Also, (iii) the polyisocyanate can be produced by reacting (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, (c) a compound having an anionic hydrophilic group and at least two active hydrogens, in which the anionic hydrophilic group of the compound having an anionic hydrophilic group and at least two active hydrogens is a salt of the anionic hydrophilic group, and (e) a trivalent or higher alcohol. In the production methods (i) and (ii), the basic compound used for neutralizing the anionic hydrophilic group is not particularly limited, and examples thereof include amines such as trimethylamine, triethylamine, tri-n-propylamine, tributylamine, N-methyl-diethanolamine, N,N-dimethylmonoethanolamine, N,N-diethylmonoethanolamine, triethanolamine, etc.; alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, etc.; ammonia, etc. Among these, tertiary amines such as trimethylamine, triethylamine, tri-n-propylamine, tributylamine, etc. are particularly preferred. In the neutralization of the anionic hydrophilic group in the manufacturing methods (i) and (ii), the amount of the neutralizing basic compound used is preferably 0.5 to 1.5 equivalents, more preferably 0.6 to 1.4 equivalents, and particularly preferably 0.7 to 1.3 equivalents relative to the anionic hydrophilic group. If the amount of the neutralizing basic compound used is less than the lower limit, the emulsification and storage stability of the urethane resin tend to decrease. On the other hand, even if the amount of the neutralizing basic compound added exceeds the upper limit, the emulsification and storage stability of the urethane resin do not improve any more, which is economically undesirable.
[0027] (urethane resin) In this specification, the urethane resin refers to a product (chain-extended product) obtained by chain-extending a neutralized product of the isocyanate-terminated prepolymer using (d) a polyamine.
[0028] (emulsification dispersion) In the chain extension of the isocyanate-terminated prepolymer neutralization product, the isocyanate-terminated prepolymer neutralization product is first emulsified and dispersed in water. The emulsification and dispersion method is not particularly limited, and includes conventionally known methods using a homomixer, a homogenizer, a disperser, etc. Even without adding an emulsifier, it is possible to emulsify and disperse in water at a temperature within the range of 0 to 40°C, and the reaction between the isocyanate group and water can be suppressed. When emulsifying and dispersing, a reaction inhibitor such as phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, paratoluenesulfonic acid, adipic acid, or benzoyl chloride may be added as necessary.
[0029] (Chain extension) Next, the neutralized isocyanate-terminated prepolymer emulsified and dispersed in water is chain-extended using polyamine (d) to form the urethane resin of the present invention. There is no particular limitation on the method of chain extension, and a method of adding polyamine (d) to an emulsion dispersion of neutralized isocyanate-terminated prepolymer to extend the chain, or a method of adding polyamine (d) to an emulsion dispersion of neutralized isocyanate-terminated prepolymer to extend the chain, is preferred. The reaction between neutralized isocyanate-terminated prepolymer and amine is usually completed at a reaction temperature of 20 to 50°C, within 30 to 120 minutes after mixing neutralized isocyanate-terminated prepolymer and polyamine (d). The chain extension may be carried out simultaneously with the emulsification dispersion, after the emulsification dispersion, or before the emulsification dispersion. In addition, when the obtained urethane resin contains an organic solvent, it is preferable to remove the organic solvent under reduced pressure at a temperature of 30 to 80°C.
[0030] Like (a) polyisocyanate, (b) polycarbonate diol having a branched structure, (c) compound having an anionic hydrophilic group and at least two active hydrogens, and the above-mentioned (e) trivalent or higher alcohol, (d) polyamine also has a plurality of reaction sites. The chain-extended product (urethane resin) of the neutralized product of the isocyanate-terminated prepolymer obtained by chain-extending the neutralized product of the isocyanate-terminated prepolymer using such (d) polyamine also has a complex structure, similar to the isocyanate-terminated prepolymer, and it is impossible to directly represent it by a general formula (structural formula).
[0031] The urethane resin thus obtained is preferably used in a state of being emulsified and dispersed in water, and the resin content concentration is not particularly limited, but is preferably 20 to 60 mass %. The resin content concentration in such an aqueous emulsion dispersion of the urethane resin can be adjusted by adding or removing water.
[0032] The aqueous urethane resin composition applied to the airbag fabric of this embodiment may contain other resins (for example, urethane resins other than the urethane resin of the present invention, acrylic resins, polyester resins, etc.), thickeners, crosslinking agents, surfactants, defoamers, leveling agents, viscoelasticity regulators, wetting agents, dispersants, preservatives, film-forming agents, plasticizers, penetrating agents, fragrances, bactericides, miticides, mildew inhibitors, ultraviolet absorbers, antioxidants, antistatic agents, flame retardants, dyes, pigments, and other various additives.
[0033] The content of the urethane resin in the solid content of the aqueous urethane resin composition is preferably 20 to 100% by mass, more preferably 40 to 100% by mass, from the viewpoints of slip resistance, breathability, and storage property of the airbag fabric. When it is 20% by mass or more, the airbag fabric has excellent slip resistance, breathability, and storage property. Furthermore, when determining the solid content in the aqueous urethane resin composition before it is applied to a base fabric, it can be calculated by measuring the mass of the residue when 5 g of the aqueous urethane resin composition is dried at 100±5°C for 3 hours.
[0034] Examples of resins other than urethane resins include acrylic resins. Examples of acrylic monomers used in acrylic resins include (meth)acrylic acid derivatives such as methyl (meth)acrylate, ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, (meth)acrylic acid, glycidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate. Here, (meth)acrylic acid refers to acrylic acid or methacrylic acid. In addition, these acrylic monomers may be used alone or in combination of two or more. Examples of copolymerization monomers used in acrylic resins include aromatic vinyl compounds such as styrene, α-methylstyrene, and p-methylstyrene; acrylamides such as acrylamide, diacetone acrylamide, methacrylamide, and maleic acid amide; heterocyclic vinyl compounds such as vinyl pyrrolidone; vinyl compounds such as vinyl chloride, acrylonitrile, vinyl ether, vinyl ketone, and vinylamide; α-olefins such as ethylene and propylene; maleic acid, fumaric acid, itaconic acid, and derivatives thereof. These copolymerization monomers may be used alone or in combination of two or more.
[0035] In the aqueous urethane resin composition, a thickener may be blended to adjust the viscosity to an appropriate level. Examples of such thickeners include alkali thickening acrylic resins, association type thickeners, water-soluble organic polymers, etc. These thickeners may be used alone or in combination of two or more. Commercially available alkali-thickening acrylic resins can be used. Nikasol VT-253A (manufactured by Nippon Carbide Industries Co., Ltd.), Aron A-20P, Aron A-7150, Aron A-7070, Aron B-300, Aron B-300K, Aron B-500 (all manufactured by Toagosei Co., Ltd.), Julimer AC-10LHP, Julimer AC-10SHP, Rheogic 835H, Junron PW-110, Junron PW-150 (all manufactured by Nippon Junyaku Co., Ltd.), Primer Examples of the resin that can be used include Primal ASE-60, Primal TT-615, Primal RM-5 (all manufactured by Rohm and Haas Japan Co., Ltd.), SN Thickener A-818, SN Thickener A-850 (all manufactured by San Nopco Ltd.), Paragum 500 (manufactured by Parachem Southern Co., Ltd.), Rheolate 430 (manufactured by Elementis Japan Co., Ltd.), and Neosticker V-420 (manufactured by Nicca Chemical Co., Ltd.). Such alkali-thickening acrylic resins are usually commercially available as emulsified dispersions of the resin, and are preferably used in an emulsified and dispersed state.
[0036] Commercially available associative thickeners can be used. Commercially available associative thickeners include Adekanol UH-450, Adekanol UH-450VF, SN Thickener 621N, SN Thickener 623N, SN Thickener 660T (all manufactured by San Nopco Ltd.), Rheolate 244, Rheolate 278, Rheolate 300 (all manufactured by Elementis Japan Co., Ltd.), DK Thickener SCT-275 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Neo Sticker N-5400 (manufactured by Nicca Chemical Co., Ltd.). Examples of the water-soluble organic polymer include natural water-soluble organic polymers, semi-synthetic water-soluble organic polymers, and synthetic water-soluble organic polymers. Examples of the natural water-soluble organic polymer include starches such as potato starch, sweet potato starch, wheat starch, rice starch, tapioca starch, and corn starch; resin polysaccharides such as gum arabic, gum tragacanth, gum karaya, and aoi; seaweed polysaccharides such as sodium alginate, carrageenan, agar (galactan), and funori; microbial fermentation polysaccharides such as xanthan gum, pullulan, curdlan, dextrin, and levan; proteins such as casein, gelatin, arabic, glue, and collagen; and pectin, chitin, and chitosan. Examples of semi-synthetic water-soluble organic polymers that can be used include cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl cellulose, and sodium cellulose sulfate; starch derivatives such as dextrin, soluble starch, oxidized starch, carboxymethyl starch, hydroxyethyl starch, hydroxypropyl starch, dialdehyde starch, starch phosphate, and acetyl starch; and propylene glycol alginate. Examples of the synthetic water-soluble organic polymer that can be used include polyvinyl alcohol, polyacrylic acid, polyacrylates, polyacrylamide, polyvinylpyrrolidone, polyvinyl alkyl ethers, maleic anhydride copolymers, maleic acid copolymers, and maleate copolymers. The amount of such a thickener (amount of non-volatile matter) to be added may be an appropriate amount depending on the viscosity of the aqueous urethane resin composition, but typically, the amount is preferably 0.1 to 40 parts by mass, and more preferably 0.3 to 30 parts by mass, per 100 parts by mass of the urethane resin.
[0037] A crosslinking agent may be added to the aqueous urethane resin composition in order to improve the breathability of the airbag. As the crosslinking agent, a carbodiimide crosslinking agent, an isocyanate crosslinking agent, an epoxy crosslinking agent, an oxazoline crosslinking agent, an aziridine crosslinking agent, a blocked isocyanate crosslinking agent, a water-dispersible isocyanate crosslinking agent, a melamine crosslinking agent, etc. are used. These crosslinking agents may be used alone or in combination of two or more. From the viewpoint of the stability of the processing liquid, it is particularly preferable to add a carbodiimide crosslinking agent. Commercially available crosslinking agents can be used. Commercially available carbodiimide crosslinking agents include Carbodilite E-02, Carbodilite SV-02, Carbodilite V02-L2, and Carbodilite V-10 (all manufactured by Nisshinbo Chemical Co., Ltd.), and NK Assist CI-02 (manufactured by Nicca Chemical Co., Ltd.). The blending amount of the crosslinking agent (blending amount of non-volatile matter) is preferably 0.1 to 30 parts by mass, and more preferably 0.5 to 15 parts by mass, per 100 parts by mass of the urethane resin, from the viewpoint of the breathability of the airbag.
[0038] The fibers used in the airbag fabric of this embodiment preferably have a thickness of 200 dtex to 800 dtex, more preferably 340 dtex to 600 dtex, and even more preferably 400 dtex to 560 dtex. If the fineness of the fibers used is 200 dtex or more, the durability required for an airbag base fabric can be satisfied, and if it is 800 dtex or less, it is possible to create a base fabric that is flexible and has good storage properties.
[0039] Examples of the fibers used in the airbag fabric of this embodiment include polyethylene terephthalate fibers and polyhexamethylene adipamide fibers. In addition, such fibers may contain various additives that are usually used to improve productivity or characteristics in the manufacturing process or processing process of raw yarn. For example, heat stabilizers, antioxidants, light stabilizers, smoothing agents, antistatic agents, plasticizers, thickeners, pigments, flame retardants, etc. can be contained.
[0040] The (tensile) strength of the fiber used in the airbag fabric of this embodiment is preferably in the range of 7.5 to 11.5 cN / dtex, more preferably 8.0 to 11.5 cN / dtex, and particularly preferably 8.2 to 11.5 cN / dtex. If the strength is 8.0 cN / dtex or more, the desired mechanical properties are obtained and the fiber is sufficient as an industrial material fiber, and if the strength is 11.5 cN / dtex or less, the fiber quality is excellent, for example, the frequency of fluff generation is low, the decrease in spinning yield is suppressed, and it does not cause weaving troubles in post-processing.
[0041] The airbag fabric of this embodiment has a weight of 150 g / m excluding the coating material. 2 ~300g / m 2 is preferred, and 170 g / m 2 ~280g / m 2 More preferably, 175 g / m 2 ~250g / m 2 More preferably, 180 g / m 2 ~210g / m 2 is even more preferable. The weight of the base fabric excluding the coating material is 150g / m 2 If it is more than 300 g / m, the airtightness required for the airbag base fabric can be satisfied. 2 If the above ratio is satisfied, it is possible to produce a lightweight base fabric.
[0042] The slippage resistance of the airbag fabric of this embodiment is preferably 1000 N to 2500 N, and more preferably 1100 N to 2000 N. If the slippage resistance is 1000 N or more, the restraint of the fibers constituting the fabric is sufficiently strong, the fibers are less likely to move even under pressure, and high airtightness can be obtained, and if it is 2500 N or less, the fibers move appropriately when folded, resulting in a fabric that is flexible and has good storability.
[0043] The air permeability of the airbag fabric of this embodiment under a differential pressure of 100 kPa is 0.01 l / cm 2 / min or less, preferably 0.008 l / cm 2 / min or less.
[0044] The coating amount of the coating material of the airbag base fabric of this embodiment is 5 g / m 2 ~15g / m 2 and preferably 8 g / m 2 ~13g / m 2 It is. Coating weight: 5g / m 2 This allows the airbag to meet the airtightness requirements, while at the same time, the 15g / m 2 By satisfying the above condition, the base fabric becomes lightweight, flexible, and easy to store. EXAMPLES
[0045] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The respective measured values in the examples were measured by the following methods.
[0046] (1) Free isocyanate group content 0.3 g of urethane prepolymer was placed in an Erlenmeyer flask, and 10 ml of 0.1N dibutylamine toluene solution was added to dissolve the urethane prepolymer. Then, several drops of bromophenol blue solution were added, and titration was performed with 0.1N hydrochloric acid methanol solution to obtain the following formula: NCO% = (a b ) × 0.42 × f / x {In the formula, a: the titration amount of 0.1N hydrochloric acid / methanol solution when only 10 ml of 0.1N dibutylamine / toluene solution is titrated, b: the titration amount of 0.1N hydrochloric acid / methanol solution when a solution in which a urethane prepolymer is dissolved is titrated, f: the factor of the 0.1N hydrochloric acid / methanol solution, and x: the amount of urethane prepolymer.} The free isocyanate group content (NCO%) was calculated by the following.
[0047] (2) Total fiber size (dtex) Measurement was performed according to the method described in JIS L 1017:2002 8.3.
[0048] (3) Tensile strength (cN / dtex) The tensile strength was measured according to the method described in JIS L 1017:2002 8.5 and divided by the total fiber size.
[0049] (4) Sliding resistance (N) Measurement was performed according to the method described in ASTM D6479.
[0050] (5) Air permeability (l / cm 2 / min) The fabric is held in a φ100mm jig, one side of the fabric is pressurized, and the differential pressure between the two sides of the fabric is adjusted to 100kPa, and the air flow rate passing through at that time is measured with a laminar flow tube type flowmeter. Five points on the same sample are measured randomly and the average value is calculated.
[0051] (6) Storage The following steps were followed: 1) Cut the base fabric to a size of 20cm x 20cm. 2) The warp direction is up and down, and the coated side is on top. 3) Make a valley fold at 5cm from both ends of the base fabric, then fold it inward. 4) Make a valley fold at 5cm from both ends of the base fabric, then fold it inward. 5) Make a valley fold at 2.5cm from both ends of the base fabric, then fold it inward. 6) Make a valley fold at 2.5cm from both ends of the base fabric, then fold it inward. 7) The sample from 6) above was placed on a flat floor surface, and a rectangular weight measuring 2 cm in height, 6 cm in width, 6 cm in depth, and 560 g in weight was placed on top of the sample. The distances from the four vertices of the underside of the weight to the floor surface were measured, and the average value of the four points was recorded as the thickness of the base fabric. The thickness was measured at five random locations for each Example and Comparative Example, and the average was calculated to determine the thickness of each Example and Comparative Example. Furthermore, the thickness of Comparative Example 1 was set to 100, and the relative values of each Example and Comparative Example were calculated.
[0052] (7) Weight of the base fabric (remainder) excluding the coating material (g / m 2 ) and coating weight (g / m 2 ) The weight of the base fabric (remainder) excluding the coating material was determined by measuring the weight per unit area of the base fabric alone before the coating material was applied, according to the method specified in JIS L-1096:2010, Method 8.3.2. The amount of coating material applied was determined from the difference in weight per unit area of the base fabric before and after application of the coating material, according to the method specified in JIS L-1096:2010, Method 8.3.2.
[0053] [Materials used in the Examples and Comparative Examples] <Organic polyisocyanate> ·H12MDI: Dicyclohexylmethane 4,4'-diisocyanate ("Desmodur W" manufactured by Covestro). ·HDI: Hexamethylene diisocyanate. <Polyol> T5652: Polycarbonate diol (made using 1,5-pentanediol / 1,6-hexanediol as raw materials) manufactured by Asahi Kasei Chemicals Corporation, product name "Duranol T5652", number average molecular weight 2,000. C2090: Polycarbonate diol manufactured by Kuraray Co., Ltd. (made using 3-methyl-1,5-pentanediol / 1,6-hexanediol as raw materials), product name "Kuraray Polyol C-2090", number average molecular weight 2,000. C3090: Polycarbonate diol manufactured by Kuraray Co., Ltd. (made using 3-methyl-1,5-pentanediol / 1,6-hexanediol as raw materials), product name "Kuraray Polyol C-3090", number average molecular weight 3,000. · UP200: Polycarbonate diol manufactured by UBE Corporation (using 2-methyl-1,3-propanediol as the raw material), product name "ETERNACOLL UP-200", number average molecular weight 2,000. C2065N: Polycarbonate diol manufactured by Kuraray Co., Ltd. (made using 2-methyl-1,8-octanediol / 1,9-nonanediol as raw materials), product name "Kuraray Polyol C-2065N", number average molecular weight 2,000. <Trivalent or higher polyhydric alcohol> · TMP: Trimethylolpropane. <Anionic hydrophilic group / active hydrogen-containing compound> ·DMPA: Dimethylolpropionic acid. <Neutralized amine> ·TEA: Triethylamine. <Chain extender> Hydrazine monohydrate. ·DETA: Diethylenetriamine. <Thickener> Neo Sticker N-5400: Manufactured by NICCA Chemical Co., Ltd. <Crosslinking agent> NK Assist CI-02: Manufactured by NICCA Chemical Co., Ltd. <Pigments> SA Green A4023: Manufactured by Mikuni Pigment Co., Ltd.
[0054] [Example 1] (Synthesis Example 1) Into a four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube was placed (b) a polycarbonate diol having a branched structure (a polycarbonate diol (2-methyl-1,3-propanediol was used as a raw material) (UBE Corporation's "ETERNACOLL 293.1 parts by mass of (UP-200, number average molecular weight 2,000), 12.3 parts by mass of dimethylolpropionic acid as a compound having an anionic hydrophilic group and at least two active hydrogens, and 98.7 parts by mass of methyl ethyl ketone were charged and mixed uniformly, and then 89.3 parts by mass of dicyclohexylmethane diisocyanate as a polyisocyanate and 0.099 parts by mass of diazabicycloundecene were added and reacted at 80°C for 240 minutes to obtain a methyl ethyl ketone solution of isocyanate-terminated urethane prepolymer with a free isocyanate group content of 2.3% by mass relative to the isocyanate-terminated prepolymer. 8.8 parts by mass of triethylamine was added to this solution and mixed uniformly, and then 632.7 parts by mass of water was gradually added to emulsify and disperse. To the obtained emulsion dispersion, 4.1 parts by mass of hydrazine monohydrate and 1.1 parts by mass of diethylenetriamine were added as a chain extender (e), and the mixture was stirred for 90 minutes to obtain a urethane resin dispersion. The urethane resin dispersion was then desolvated at 40°C under reduced pressure to obtain an aqueous dispersion of urethane resin with a resin content of 40.0% by mass. (The proportion of (b) in the total amount of compounds having a hydroxyl group capable of reacting with an isocyanate group in the synthesized urethane resin, the proportion of structural units derived from a diol having a branched structure in the structural units derived from the diol of (b), and the proportion of (e) in the total amount of compounds having a hydroxyl group capable of reacting with an isocyanate group in the synthesized urethane resin are shown in the tables in the examples.)
[0055] (Water-based urethane resin composition 1) 800 parts by mass of the aqueous dispersion of the urethane resin obtained in Synthesis Example 1, 3.8 parts by mass of a thickener ("Neosticker N-5400" manufactured by Nicca Chemical Co., Ltd.), and 1.6 parts by mass of a pigment ("SA Green A4023" manufactured by Mikuni Pigment Co., Ltd.) were mixed to prepare an aqueous urethane resin composition 1.
[0056] Next, polyhexamethylene adipamide fiber with a total fineness of 470 dtex, 136 filaments, and a tensile strength of 8.3 cN / dtex was shaped without twist or size, and the same yarn was used as the weft yarn to make a plain weave on a water jet loom. The fabric was then scoured and set to a base fabric weight of 200 g / m 2 Next, the aqueous urethane resin composition 1 was applied to one surface of the substrate by knife coating in an amount of 11 g / m 2 After coating so as to obtain a base fabric for an airbag, the base fabric was treated at 190° C. for 1 minute using a pin tenter heat treatment machine. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.
[0057] [Examples 2 to 9, Comparative Example 1] In Synthesis Examples 2 to 7, the types and amounts of (a) polyisocyanate, (b) polycarbonate diol having a branched structure, (c) compound having an anionic hydrophilic group and at least two active hydrogens, (d) polyamine having two or more amino groups and / or imino groups, (e) trivalent or higher alcohol, and neutralized amine shown in Table 1 were used, but the same preparations were used as in Synthesis Example 1, and the reaction was continued until the free isocyanate group content relative to the isocyanate group-terminated prepolymer shown in the tables of Examples and Comparative Examples, thereby obtaining an aqueous dispersion of a urethane resin. In Comparative Synthesis Example 1 and Preparation Synthesis Example 1, (a) polyisocyanate, (b)' polycarbonate diol other than (b), (c) compound having an anionic hydrophilic group and at least two active hydrogens, (d) polyamine having two or more amino groups and / or imino groups, (e) trivalent or higher alcohol, and neutralized amine were used in the types and amounts shown in the tables of Examples and Comparative Examples, but the same materials were charged as in Synthesis Example 1 and reacted until the free isocyanate group content relative to the isocyanate group-terminated prepolymer shown in the tables of Examples and Comparative Examples was obtained, thereby obtaining an aqueous dispersion of a urethane resin. For aqueous urethane resin compositions 2 to 9 and comparative aqueous urethane resin composition 1, the urethane resin water dispersion, thickener, crosslinker, and pigment shown in the table were mixed in the same manner as for aqueous urethane resin composition 1 to prepare various aqueous (or comparative aqueous) urethane resin compositions. The obtained aqueous urethane resin composition was applied to the same base fabric as in Example 1, and the same processing treatment was carried out. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.
[0058] [Examples 10 and 11] The amount of coating material applied to the base fabric is 6g / m 2 , 15g / m 2 Except for the above, the same procedure as in Example 7 was carried out. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.
[0059] [Example 12] Polyethylene terephthalate fibers with a total fineness of 550 dtex, 140 filaments, and a tensile strength of 8.0 cN / dtex were warped without twist or size, and the same yarn was used for the weft, woven into a plain weave on a water jet loom, scoured, and set, resulting in a base fabric weight of 243 g / m 2 Aqueous dispersion 7 of urethane resin was added to the base fabric in an amount of 11 g / m in the same manner as in Example 1. 2 The coating was carried out in the same manner as in Example 1, and the coating was carried out in the same manner as in Example 1. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.
[0060] [Comparative Examples 2 and 3] The amount of coating material applied to the base fabric is 3g / m 2 , 20g / m 2 The same procedure as in Example 7 was carried out except that (solid content) was used. The physical properties of the obtained base fabric are shown in Tables 1 to 3 below.
[0061] [Table 1]
[0062] [Table 2]
[0063] [Table 3] [Industrial Applicability]
[0064] The airbag fabric according to the present invention is a base fabric that combines high airtightness, good storage property, and light weight, and can be suitably used for airbag applications having high storage property, light weight, and low breathability.
Claims
1. The airbag fabric comprises a base fabric and a cured product of an aqueous urethane resin composition applied to at least one surface of the base fabric, the aqueous urethane resin composition having the following properties: (a) a polyisocyanate, (b) a polycarbonate diol having a branched structure, and (c) a compound having an anionic hydrophilic group and at least two active hydrogens; The isocyanate-terminated prepolymer obtained by reacting the above as an essential component with the following: (d) a polyamine having two or more amino groups and / or imino groups; The aqueous urethane resin composition contains a urethane resin obtained by reacting 2 ~15g / m 2 An airbag base fabric, characterized in that it is coated.
2. The airbag fabric according to claim 1, wherein the (b) polycarbonate diol having a branched structure has a structural unit derived from a diol having a branched structure and having 3 to 10 carbon atoms.
3. The (b) polycarbonate diol having a branched structure has a structural unit derived from a diol having 3 to 10 carbon atoms and a linear structure. The airbag base fabric according to claim 1 or 2.
4. The aqueous urethane resin composition further comprises the following components in addition to the components (a), (b), and (c): (e) trihydric or higher alcohol, The airbag fabric according to claim 1 or 2, comprising a urethane resin obtained by reacting (d) with an isocyanate-terminated prepolymer obtained by reacting (a) and (b) as an essential component.
5. The airbag fabric according to claim 1 or 2, wherein the airbag fabric has a slip resistance of 1000N to 2500N.
6. The air permeability of the airbag fabric under a differential pressure of 100 kPa is 0.01 l / cm 2 The airbag base fabric according to claim 1 or 2, wherein the airbag base fabric has a viscosity of 100 / min or less.
7. The airbag fabric according to claim 1 or 2, wherein the airbag fabric is made of a raw yarn having a fineness of 200 dtex to 800 dtex.
8. The airbag fabric according to claim 1 or 2, wherein the fibers constituting the fabric are polyethylene terephthalate fibers or polyhexamethylene adipamide fibers.
9. The airbag fabric according to claim 1 or 2, wherein the tensile strength of the fibers constituting the base fabric is 7.5 cN / dtex to 11.5 cN / dtex.
10. The weight of the remainder excluding the cured product of the aqueous urethane resin composition is 150 g / m 2 Up to 300 g / m 2 The airbag fabric according to claim 1 or 2.
Citation Information
Patent Citations
Base fabric for air bag and air bag
JP2009062643A
Base cloth for airbag, airbag composed of the same, and manufacturing method of the same
JP2011168131A
Cited By
Thermoplastic polyurethane resin, method for producing the same, and molded product
JP7909103B1